The Child Sport Concussion Assessment Tool (Child SCAT3): normative values and correspondence between child and parent symptom scores in male child athletes. Issue 1 (21st August 2015) - Porter, Shaun; Smith-Forrester, Jenna; Alhajri, Najah; Kusch, Cody; Sun, Jonathan; Barrable, Bill; Panenka, William J; Virji-Babul, Naznin
Abstract : Background: Children and youth are at increased risk of sustaining sport-related concussions. There is a need to develop age-specific tools to evaluate the effects of concussion. The objective of this study was to determine normative values for the Child Sport Concussion Assessment Tool (Child SCAT3) in child athletes and evaluate the symptom scoring agreement between the child and parent. Methods: Child SCAT3 was administered to ice hockey players enrolled in a regional minor hockey association. Statistical analyses were performed to evaluate the differences between child and parent reporting as well as those based on age. Results: 227 athletes (7–12 years of age) completed the Child SCAT3. 29 players reported a history of concussion. For the objective components, the average total Standard Assessment of Concussion adapted to a child version (SAC-C) score of 24.4 was made up by orientation (3.7), immediate memory (12.9), concentration (3.8) and delayed recall (3.9) sections. Average errors in the modified Balance Error Scoring System (BESS) were 1.6, tandem gait time 14.9 s and coordination score 0.95. For the subjective component, children reported an average of eight symptoms and a severity of 11; parents reported seven symptoms with a severity of 9. Overall, children reported higher symptom severity in comparison with their parents. In addition, parents significantly underestimated both physical and sleep-related symptoms in comparison with the children's scores. Conclusions: Results provide representative scores for the Child SCAT3 in young male ice hockey players. Clinicians should be aware that parents tend to underestimate their child's symptoms and symptom severity, particularly in the domains of physical symptoms and sleep. Encouraging objective symptom documentation with sleep or pain diaries, for example, may be useful for reliable clinical assessment in this age group.